ENHANCING MOTIVATION THROUGH STUDENT-TEACHER FACEBOOK RELATIONSHIPS - Smith, Brian E. (PEOPLE: International Journal of Social Sciences, 2015)
Teacher accessibility is not limited to the time spent in the classroom, and the use of Facebook as a tool for motivation between teachers and students, through immediacy and sincere engagement, is invaluable. This paper aims to explain the benefits of using Facebook, discuss set up issues and present feedback from students on its implementation. It also focuses on the establishment of social networking between students and teachers as being advantageous in terms of empathy, connection and empowering students to express themselves. Various research in the field of motivation, and reflections on my personal experience with Facebook’s use will be expanded upon.